A Holistic Approach to Stormwater Green Infrastructure - Mirza, Sana; Nie, Jing; Viteritto, Michael; Feng, Huan (Journal of Environmental Science and Engineering Technology, 2020)
One of the factors that threaten fresh water quality is the input of anthropogenic nutrients, a problem heightened in urban areas with lots of impervious surfaces. The implementation of stormwater green infrastructure allows stormwater runoff to be filtered before entering waterways, reducing nutrient input. Stormwater green infrastructure includes installations such as green roofs, green alleyways, and parks which can provide environmental, mental and physical health benefits to local residents who may have lacked access to green space. However, such installations can also have the counter intuitive effect of gentrification, termed the ‘green space paradox’. Through the review of published literature and case studies, a holistic design of stormwater green infrastructure implementation is presented in this study, which includes public participation, sustainability, and equity of distribution.